The Bantay Bata 163 Program and the level of cooperation of the government and other NGOs in the operations of the program (Region VI). - Crudo, Dexter A.
Using interviews and library work, the signatories of the memorandum of agreement and the Bantay Bata 163 program were the focus of the study. The objectives were to explain the plight of the children in Region VI (Western Visayas), to describe the nature of Bantay Bata 163 program, to determine the mechanics of the operations of the Bantay Bata 163 program, to analyze the actual vs. what is written in the memorandum of agreement signed between the Bantay Bata 163 and the government and between the Bantay 163 and the NGOs, and to be able to determine the bearing of the signatories in the operations of the program. (p)The 1995 survey of the National Statistics Office provided the information regarding the plight of the children in Region VI (Western Visayas). As of July 1995, the total number of children was 2,154,000 and out of it, 422,000 children were working. Farming was the top choice industry among male and female child workers. All of the working children had at least an elementary education with the educational level Grade 1-5 as the most common educational attainment among the child workers. 50 of the working children preffered to continue working and 48.7 would stop working if they were given the chance not to continue working. (p)The Bantay Bata 163 program is a child abuse intervention program that operates a hotline to give easy access to efficient and immediate response to Filipino children in crisis. The services they offer are Hotline Services, Rescue Operations, Walk-in Desk, Medical Assistance, Children's Home, and Counseling. (p)The majority of the signatories scored excellent in their level of cooperation and there were few that scored neutral. The three law enforcement agencies, NBI, CHR and PNP, are important in every rescue operations. It is because the law mandates them and Bantay Bata is not. (p)The researcher concluded that the 1987 Constitution and the passage of the R.A. 7610 or the Local Government Code in 1991 provided the legal framework for the government and NGOs to work together for development and other concerns. Networking would be able to provide additional resources to those who do not have.